PENGGUNAAN MODEL PEMBELAJARAN KOOPERATIF TIPE NHT (NUMBER HEAD TOGETHER) DALAM MENINGKATKAN HASIL BELAJAR SISWA PADA MATA PELAJARAN SEJARAH KELAS XI DI SMA N 1 BENAI - Ariani, Melda; Ibrahim, Bedriati; Oemar, Kamaruddin (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstrack: The implementation of a learning process the ultimate goal is that students know and understand what the teacher taught, learning is the key to students success, students will succsessful if followed well and active learning. The purpose of this research is 1) to determine the level of activity of the teacher using cooperative learning model NHT in SMA N 1 Benai 2) to determine the level of activity of the students using cooperative learning model NHT in SMA N 1 Benai 3) to determine the extent of cooperative learning model NHT can improve student learning result in the classroom XI SMA N 1 Benai. In this research uses type class act research method that uses qualitative descriptive research.This research does through two cyles and every cycles has plenning, applying, monitoring and reflecting. Subject in this research is students class XI SMA N 1 Benai. Data analysis technique apply descriptive quantitatif analysis has observation and study result test and descriptive qualitative analysis. The result of research show teacher activity during two sycles increased at 22 with good category in cycle I and 28 with very good category in cycle II. Students activity increased by a score 450 with enought category in cycle I and 687 with good category in cycle II. The Students learning result also increased for two sycles in sycle I with an average value 73,5 increased to 87,60 in cycle II. So it can be conclude that through by using cooperative learning model NHT can increase teacher activity, students activity and students learning result in the subjects of history at class XI in SMA N 1 Benai.Key word : NHT Leaening Models, History Studies, Study Result